Dating App Facilitated Sexual Assault: A Retrospective Review of Sexual Assault Medical Forensic Examination Charts. Issue 9 (May 2023) - Valentine, Julie L.; Miles, Leslie W.; Mella Hamblin, Kristen; Worthen Gibbons, Aubrey
Dating app facilitated sexual assault (DAppSA) is a concerning phenomenon with minimal published research. This retrospective study explored if DAppSAs were different than other sexual assaults (SAs) committed by acquaintances through a review of 3, 413 sexual assault medical forensic examination (SAMFE) charts from 2017 to 2020 in a Mountain West state in the United States. Routine Activities Theory and Confluence Model of sexual aggression provided the theoretical framework for the study. Inclusion criteria for DAppSA cases included (1) victim was 14 years of age or older; (2) victim indicated meeting the perpetrator on a dating app; (3) SA occurred at initial in-person meeting; and (4) victim had a SAMFE with SA kit evidence collection. DAppSAs ( n  = 274) represented 8.02% of overall cases and 13.92% of acquaintance SAs ( n  = 1, 968). DAppSA victims had unique characteristics including a higher percentage of male victims (7.5%), college students (22.2%), and victims with self-reported mental illness (MI) (59.6%). Victims were less likely to fight back during the assault with lower percentages of kicking (5.8%) and hitting (9%). DAppSA victims and perpetrators were less likely to use drugs or alcohol before or during the assault. DAppSAs were found to be more violent SAs with increased strangulation (32.4%); assaultive/penetrative acts; and victim injuries, especially anogenital and breast injuries. Unique and troubling differences were found in DAppSA cases than other SAs committed by acquaintances. Due to the increased violent nature of DAppSAs, the researchers propose that sexual predators use dating apps as hunting grounds for vulnerable victims. Recommendations to address dating app safety concerns, influence dating app usage policies, and improve care to survivors are discussed through systems-based and trauma-informed approaches.